Indefinite Pronouns - Haspelmath, Martin (Oxford Studies in Typology and Linguistic Theory, 1997)
Most of the world's languages have indefinite pronouns, that is, expressions such as someone, anything, and nowhere. This book presents an encyclopaedic investigation of indefinite pronouns in the languages of the world, mapping out the range of variation in their functional and formative properties. It shows that cross-linguistic diversity is severely constrained by a set of implicational universals and by a number of unrestricted universals. Topics include formal and functional types of indefinite pronoun, theoretical approaches to the functions of indefinite pronouns, the grammaticalization of indefinite pronouns, and negative indefinite pronouns.